Histopathological Features of Basal Cell Carcinoma and Defect Reconstruction Using Rhomboid Flap: A Case Report - Molla Andriska Dewi; T. Ibnu Alferraly; Remenda Siregar (GLOBAL HEALTH SCIENCE GROUP, 2025)
Basal cell carcinoma (BCC) is the most prevalent type of nonmelanoma skin cancer, primarily associated with chronic ultraviolet exposure and typically affecting elderly individuals. This case report aims to describe the clinicopathological features and management of BCC in an 81-year-old woman who presented with a hyperpigmented nodule on the left mandibular region. A comprehensive approach was undertaken, including clinical assessment, dermoscopic evaluation, and histopathological examination. The lesion was surgically excised, and the resulting defect was reconstructed using a rhomboid flap. This procedure achieved complete tumor clearance and successful defect closure, with favorable aesthetic and functional outcomes and no postoperative complications. This case highlights the effectiveness of rhomboid flap reconstruction in restoring tissue intergrity following BCC excision, emphasizes the improtance of early diagnosis and histopathology confirmation, and highlights the role of surgical technique in optimizing patient prognosis. Furthermore, the findings contribute to the body of evidence supporting the rhomboid flap as a reliable option for facial reconstruction following oncologic surgery, enhancing postoperati ve recovery and quality of life for patients undergoing facial oncologic surgery.